On the status of the tribes Orthognathini and Rhinostomini (Coleoptera: Curculionidae: Dryophthorinae) - Morrone, Juan J.; Cuevas, Perla I. (Zootaxa, 2009)
A cladistic analysis is performed of the four genera of the tribe Orthognathini of the curculionid subfamily Dryophthorinae, specifically to assess whether the tribe constitutes a monophyletic group or whether the genus Rhinostomus falls outside it into a separate tribe, as advocated in some classification systems. The analysis based on 27 morphological characters revealed that Orthognathini is indeed a monophyletic group, with the phylogenetic sequence Rhinostomus (= Yuccaborus), Sipalinus, Mesocordylus and Orthognathus. The basal position of Rhinostomus with respect to the other genera may warrant recognition of a separate subtribe, Rhinostomina, for it. Taxonomic synopses of the tribe and subtribes and a key to the genera are provided.